2023
DOI: 10.1097/psy.0000000000001181
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Events, Posttraumatic Stress Disorder, and Central Sensitization in Chronic Pain Patients of a German University Outpatient Pain Clinic

Abstract: ObjectivePosttraumatic stress disorder (PTSD) and traumatic life events are often coupled to chronic pain, possibly linked by central sensitization. We wanted to assess the prevalence of traumatic events and PTSD in chronic pain patients of a German university hospital outpatient pain clinic. Moreover, we evaluated the extent of indicators and co-occurring traits of central sensitization in comorbid patients.MethodsWe retrospectively divided 914 chronic pain patients into four groups depending on their trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…One study conducted by Bhat and Rangaiah [54], showed that 49.81% of young adults (19-24 years) (n = 797) encountered at least one traumatic event, with the most common event being the death of a close one, serious illness, witnessing the injury or killing of others, and coming close to being injured or killed. Substantial literature has revealed that traumatic events are one of the risk factors leading to chronic pain [55][56][57]. In one of the studies conducted in the Norway reported that the exposure to traumatic events and PTSD were significantly associated with more severe physical pain, and PTSD significantly moderated the relationship between trauma exposure and pain [58] and in one of the cohort studies that included 2021 participants from the USA observed over time that after traumatic stress exposure, identified individuals with greater pain severity [59].…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted by Bhat and Rangaiah [54], showed that 49.81% of young adults (19-24 years) (n = 797) encountered at least one traumatic event, with the most common event being the death of a close one, serious illness, witnessing the injury or killing of others, and coming close to being injured or killed. Substantial literature has revealed that traumatic events are one of the risk factors leading to chronic pain [55][56][57]. In one of the studies conducted in the Norway reported that the exposure to traumatic events and PTSD were significantly associated with more severe physical pain, and PTSD significantly moderated the relationship between trauma exposure and pain [58] and in one of the cohort studies that included 2021 participants from the USA observed over time that after traumatic stress exposure, identified individuals with greater pain severity [59].…”
Section: Discussionmentioning
confidence: 99%
“…If this system collapses under a chronic stress condition, the allostatic load can no longer be coped with and psychiatric comorbidities (depression, anxiety disorder, post-traumatic stress disorder) may manifest 9 47 48 . There is a broad overlap between these disorders and chronic pain 23 . Accordingly, experimental and clinical studies show that especially patients with high central stress levels benefit from cannabinoid therapy.…”
Section: Chronic Pain Chronic Stress and The Endocannabinoid Systemmentioning
confidence: 99%
“…In a cohort of 914 patients with chronic pain from a German university hospital outpatient clinic, positive correlations were found between observed intensity of trauma and pain area overlap, pain widespreadness, maximum pain, sleep disturbance, pain disability index, stress, anxiety, depression, and somatization [23]. The increased pain area and pain widespreadness, as well as the effects on clinical endpoints such as pain intensity, sleep disturbance, symptom burden disability, and stress, are consistent with the concept of central sensitization in patients with PTSD [23].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic stress occurs when an individual experiences sustained emotional or physiological challenges continuously over a significant period of time, leading to "wear and tear on the body" (35). Long-term stress has been shown to sensitize individuals to pain, a phenomenon known as stressinduced hyperalgesia (36)(37)(38)(39). Bolstering this hypothesis, Ide et al showed that unpredictable chronic mild stress reduced the pain-relieving effects of morphine in mice (40).…”
Section: Role Of Chronic Stress In Vulnerability For Chronic Painmentioning
confidence: 99%